Modelling Forest Systems. Workshop on the Interface Between Reality, Modelling and the Parameter Estimation Processes, Sesimbra 2003
DOI: 10.1079/9780851996936.0011
|View full text |Cite
|
Sign up to set email alerts
|

Mapping lodgepole pine site index in Alberta.

Abstract: We demonstrate the methods and results for broad-scale mapping of forest site productivity for the Canadian province of Alberta. Site index (SI) data were observed for lodgepole pine (Pinus contorta var. latifolia) based on stem analysis (observed height at an index breast height age of 50 years). A total of 2624 trees at nearly 1000 site locations were available for the analysis. Mapping methods were based on ANUSPLIN, Hutchinson's thin-plate smoothing spline in four dimensions (latitude, longitude, elevation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…In addition to confirming the importance of geographic variables, results from this study also indicate that (1) natural subregions are good pre- dictors and that (2) the addition of synoptic variables of soil moisture and nutrients explained only a minor component of the variation in site index. The results shown in Table 3 suggest that with every 100 m increase in elevation, lodgepole pine site index decreases about 0.6 m. This outcome is similar to that found by Monserud and Huang (2002). Lower temperature and shorter growing season at higher elevation (Table 1) is likely responsible.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In addition to confirming the importance of geographic variables, results from this study also indicate that (1) natural subregions are good pre- dictors and that (2) the addition of synoptic variables of soil moisture and nutrients explained only a minor component of the variation in site index. The results shown in Table 3 suggest that with every 100 m increase in elevation, lodgepole pine site index decreases about 0.6 m. This outcome is similar to that found by Monserud and Huang (2002). Lower temperature and shorter growing season at higher elevation (Table 1) is likely responsible.…”
Section: Discussionsupporting
confidence: 75%
“…In a recent study based on a large data set collected across the natural distribution range of lodgepole pine in Alberta, Monserud and Huang (2002) also found that geographic factors (elevation, latitude, longitude) were significant predictors of lodgepole pine site index. Using a much larger network of stem analysis plots (nearly 1000), they mapped lodgepole pine site index across Alberta with a thin-plate smoothing spline using only elevation, latitude, and longitude; root mean square residual was 1.16 m (Monserud and Huang 2002). Similarly, a study for inland Douglas-fir in northern Idaho and northwestern Montana, Monserud et al (1990) also reported that elevation together with latitude and longitude explained 39% of the total variation in site index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not to say that precipitation and winter temperatures are not important factors in the fundamental causes of lodgepole pine productivity. Based on the hand-drawn Alberta lodgepole pine distribution map from earlier work (Monserud and Huang 2003), 80% of the pixels (picture elements) were within the DI limits of 0.9-2.6 8CÁmm -1 . Next, the natural distribution of lodgepole pine was examined as a function of DI.…”
Section: ½1mentioning
confidence: 98%
“…As these factors can be spatially linked, potential site productivity for a given tree species can be predicted and mapped at the landscape level (Gustafson et al 2003, Monserud andHuang 2003). Such flexibility makes the geocentric approach an attractive alternative over the phytocentric approach from the perspective of large-scale integrated planning and management of forest resources.…”
Section: The Geocentric Approachmentioning
confidence: 99%